SISTEM PERINGATAN DINI BANJIR BERDASARKAN KETINGGIAN AIR, DEBIT AIR DAN CURAH HUJAN DILENGKAPI DENGAN SISTEM MONITORING DATA SENSOR - Abdullah Abdullah; Rizki Fitriana (UIN Sumatera Utara, 2020)
The river often overflows during the rainy season and floods very detrimental. For the community. Therefore designed a monitoring tool and water discharge and rainfall intensity. This tool is constructed using a combination of water level sensors, ultrasonic sensors (SRF-05) and water flow to produce a monitoring system that provides participation early banji, make a program that can display the results surface monitoring and air discharge. See flood early and learn about the performance of surface monitoring systems and flood air discharge with faster rainfall and understand the microcontroller in measuring and controlling system. Tests carried out with aquarium prototypes and carried out. Measurement for one day on a continuous basis. Test results show that this tool can be updated reminded of flood early efficiently. With Thus, the tool designed is able to monitor the height of water activity, discharge and rainfall in rivers, programs are made capable run the designed tool and the results of monitoring can be accessed through LCD that is able to visualize water activities and this early permit system able to work to measure the height and air discharger rain and be able to implement data input from sensors too displays data on the state of the river so that it can be monitored through a computer. As well as a microcontroller capable of measuring and controlling the system accurately and input data from sensors in height and air discharge measurements as well. Rainfall intensity can be monitored via computer. Keywords: Rainfall, Water Discharge, Water level, Monitoring